(untitled) (International Journal of Engineering and Computer Science, 2015)
The provisioning of basic security mechanism such as authentication and confidentiality in the publish/subscribe system. Authentication in this system is difficult to achieve due to the loose coupling between publishers and subscribers. Likewise, Confidentiality of events and subscriptions conflicts with content-based routing. To ensure authentication and confidentiality in broker less publish/subscribe system we adopt pairing based cryptography mechanism. Furtherly, broadcasting encryption algorithm is adapted to provide subscription confidentiality by clustering subscribers according to their subscription by providing a private key with their credentials. Sowe adapt identity based encryption for providing private key to the subscribers with their credentials based on their identity (e.g. e-mail). This technique enables efficient routing of encrypted events, provides thorough analysis of various attacks on subscription confidentiality and a fine grained key management. Moreover, the evaluations show that providing security is affordable w.r.t. 1) throughput of the proposed cryptographic primitives, and 2) delays incurred during the construction of the publish/subscribe overlay and the event dissemination.